Prospect of Biodiesel production from Algae as a renewable energy source in Sarawak - Abu Saleh, Ahmed; Ricky Stu, Anding; Sinin, Hamdan; ABM Sharif, Hossain; Syed Tarmizi, Syed Shazali (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.